Auditors' responsibility in assessing going concern assumption affected by Covid-19 - Milica orević; Tadija ukić (Economic Themes, 2021)
The Covid-19 pandemic and the measures introduced to prevent its further spread have undoubtedly led to significant business uncertainties regarding the going concern principle. Not only has the global economy experienced negative effects of the pandemic, but a number of professions as well, including auditing. With their significant responsibility in assessing the going concern, auditors face a number of challenges. The aim of this paper is to point out the need for more extensive consideration of auditors in assessing the going concern, as well as the challenges auditors face in a pandemic and the ways in which they overcome these limitations.
Keywords: M42; 330; going concern; auditors' approach; Covid-19